HIV prevention - Newell, Marie-Louise; Tanser, Frank (Clinical insights (London, England), 2013)
This book provides a synthesis of the latest information on this fast changing area from a distinguished set of experts in all fields of HIV prevention - biomedical as well as behavioral.